1986
DOI: 10.1093/oxfordjournals.jbchem.a121785
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Lysine1 and Lysine7 Residues of Bovine Pancreatic Ribonuclease in the Enzymatic Activity

Abstract: In order to investigate the roles of Lys1 and Lys7 of RNase A in the enzymatic activity, four S-peptide derivatives were prepared and their abilities to activate S-protein were measured. They are 1-norleucine-S-peptide, 7-norleucine S-peptide, 1,7-di-norleucine-S-peptide, and tri-N-acetyl S-peptide. From the analyses of the relative activity and kinetic parameters of RNase S' derivatives with UpU, UpU greater than p, and UpUpU greater than p, it was concluded that Lys7 of RNase A is a binding site for 3'-phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several previous reports support this role for Lys-7. Thus experiments with oligomeric substrates and an RNAase S' with a modified Speptide ([7-norleucine]S-peptide) clearly support the involvement of Lys-7 in the interaction with the phosphate group that binds in P2 (Irie et al, 1986). Detailed X-ray-crystallographic studies of a complex between RNAase A and d(pA)4 indicate that the phosphate adjacent to that occupying p1, i.e.…”
mentioning
confidence: 78%
“…Several previous reports support this role for Lys-7. Thus experiments with oligomeric substrates and an RNAase S' with a modified Speptide ([7-norleucine]S-peptide) clearly support the involvement of Lys-7 in the interaction with the phosphate group that binds in P2 (Irie et al, 1986). Detailed X-ray-crystallographic studies of a complex between RNAase A and d(pA)4 indicate that the phosphate adjacent to that occupying p1, i.e.…”
mentioning
confidence: 78%
“…It seems unlikely that this increase resulted from the use of deoxyadenosine, since no difference in the kinetic parameters for UpA and UpdA with RNase A have been found (2). Previously, such improved catalytic efficiency with elongated substrates has been explained by the interaction between the additional phosphate groups and positively charged subsites on the enzyme (44,45). In this model is bound by Lys-66, whereas the one on the 3'-side of the purine (the p2-subsite) is bound by Lys-7 and Arg-10.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction yielded a major derivative (derivative II) with the nucleotide label attached to the ␣-amino group. Different studies suggested that the phosphate group was bound in a specific phosphate-binding subsite, p 2 , and that Lys-7 and Arg-10 were involved in that subsite (Arú s et al, 1981;Irie et al, 1986;de Llorens et al, 1989; Richardson et al, 1990). The structure of derivative II was recently solved by x-ray crystallography (Boqué et al, 1994), and the structure found is in accordance with the location of p 2 , B 3 , and R 3 2 subsites at the N-terminal region of the protein.…”
mentioning
confidence: 99%